Formal and Final Causation in Systems Biology: Denis Noble and Denis Walsh’s Reinterpretation against Gene-Centered Reductionism - García-López, Mathias (2026)
This article addresses the philosophical recovery of the Aristotelian formal and final causes within contemporary theoretical biology, and their capacity to overcome the explanatory limitations of the gene centered paradigm inherited from the Modern Synthesis. It proceeds from the premise that linear efficient causation, understood as the unidirectional flow of information from genotype to phenotype, proves insufficient to account for phenomena such as morphogenesis, phenotypic plasticity, and physiological robustness, which demand a systemic and multidirectional understanding of living organization. Drawing on Denis Walsh's account of natural teleology and organismic agency, and on Denis Noble's account of downward causation and the absence of any privileged level of biological causation, the article examines how the organism, understood as a self regulating totality, exerts a formal causal function over its own molecular components. It further analyzes the empirical mechanisms that support this reinterpretation, including epigenetic regulation, physiological homeostasis, and developmental canalization. To this end, an organicist approach to biological explanation is adopted, understood as the theoretical framework that conceives the living organism as a causally autonomous unit whose internal finality, or immanent teleology, orients, without mechanically determining, the entire set of processes that constitute it as a living system.